Effect of Isocenter Placement at Nasion and Symphysis Menti on the Quality of MRI Images in Cases of Nasopharyngeal Cancer - Nurbaiti, Nurbaiti; Zola, Thifal Humaira (Majalah Kedokteran Bandung, 2025)
Magnetic Resonance Imaging (MRI) examinations require precise placement of the isocenter as it directly influences the quality of MRI images. In the context of nasopharyngeal MRI examinations, different opinions regarding the optimal placement of the isocenter exist. Currently, two methods of isocenter placement are commonly applied, i.e., nasion and symphysis menti isocenter placement. This study aimed to analyze how these different isocenter placements affect the quality of MRI images in T2 Turbo Spin Echo sequences of the nasopharynx in the coronal plane. This study was conducted in June 2023 at the Radiology Installation of Dharmais Cancer Hospital, Jakarta, Indonesia. This study used the quantitative experimental approach. Six samples were purposively selected from nasopharyngeal cancer patients, and two treatments were conducted: isocenter placement at the nasion and isocenter placement at the symphysis menti. Data processing was performed using a statistical software. The results of the Wilcoxon test for image quality from the perspective of the signal-to-noise ratio (SNR) yielded a p-value of 0.173, which was greater than 0.05, indicating that there was no significant difference in image quality as measured by the SNR between the two isocenter placements. Similarly, the paired sample t-test for image quality in terms of the contrast-to-noise ratio (CNR) resulted in a p-value of 0.610, which was also greater than 0.05. This demonstrated no significant difference in the image quality between the two isocenter placements from the perspective of the CNR measures. Thus, both isocenter placements resulted in comparable image quality.